Endosymbiotic bacteria of the boar louse Haematopinus apri (Insecta: Phthiraptera: Anoplura) - Nishide, Yudai; Oguchi, Kohei; Murakami, Maria; Moriyama, Minoru; Koga, Ryuichi; Fukatsu, Takema (Frontiers in Microbiology, 2022)
Insects exclusively feeding on vertebrate blood are usually dependent on symbiotic bacteria for provisioning of B vitamins. Among them, sucking lice are prominent in that their symbiotic bacteria as well as their symbiotic organs exhibit striking diversity. Here we investigated the bacterial diversity associated with the boar louse Haematopinus apri in comparison with the hog louse H. suis. Amplicon sequencing analysis identified the primary endosymbiont predominantly detected from all populations of H. apri with some minor secondary bacterial associates. Sequencing and phylogenetic analysis of bacterial 16S rRNA gene confirmed that the endosymbionts of the boar louse H. apri, the hog louse H. suis and the cattle louse H. eurysternus form a distinct clade in the Gammaproteobacteria. The endosymbiont clade of Haematopinus spp. was phylogenetically distinct from the primary endosymbionts of other louse lineages. Fluorescence in situ hybridization visualized the endosymbiont localization within midgut epithelium, ovarial ampulla and posterior oocyte of H. apri, which were substantially the same as the endosymbiont localization previously described in H. suis and H. eurysternus. Mitochondrial haplotype analysis revealed that, although the domestic pig was derived from the wild boar over the past 8,000 years of human history, the populations of H. apri constituted a distinct sister clade to the populations of H. suis. Based on these results, we discussed possible evolutionary trajectories of the boar louse, the hog louse and their endosymbionts in the context of swine domestication. We proposed ‘Candidatus Haematopinicola symbiotica’ for the distinct clade of the endosymbionts of Haematopinus spp.